A population-based study of health-promoting behaviors and their predictors in Iranian males, 2019 - Fovziye Sanaati; Mehrnaz Geranmayeh; Zahra Behboodi Moghadam; Armin Zareiyan; Keshvar Samadaee Gelehkolaee; Mojgan Mirghafourvand (BMC, 2021)
Abstract Background Health-promoting lifestyle (HPL) is any measure taken to maintain a person's health. The most important and influential factor in maintaining and enhancing health are health-promoting behaviors (HPB). This study aimed to determine HPB and their predictors among Iranian men. Methods In this cross-sectional study, 783 Iranian men, living in Tehran, were selected, using multistage cluster sampling. The employed questionnaires, namely the sociodemographic questionnaire, Health-Promoting Lifestyle Profile II (HPLP-II), and the second part of the Personal Resource Questionnaire (PRQ 85-Part 2), were completed through interviews. The relationship between the dependent variables (HPLP-II and its subdomains) and independent variables (sociodemographic characteristics and social support) was investigated using the adjusted General Linear Model (GLM). Results The mean ± standard deviation of the total HPLP-II score was 2.72 ± 0.44 in the range of 1-4. Among the six dimensions of the HPB, the participants achieved the highest score (3.00 ± 0.52) and lowest score (1.96 ± 0.56) in spiritual growth and physical activity, respectively. The Pearson test showed that the perceived social support was significantly correlated with HPLP-II (r = 0.23; p < 0.001) and all of its subdomains (r = 0.09-0.24; p < 0.001). Based on the adjusted general linear model, social support, age, job, and income adequacy were the predictors of HPL in men and could explain 30.9% of the variance of the HPL score. Conclusions The research findings confirmed the importance of social support and modifying variables (social and personal) in the incidence of HPB in men.